HPV integration generates a cellular super-enhancer which functions as ecDNA to regulate genome-wide transcription - Tian, Rui; Huang, Zheying; Li, Lifang; Yuan, Jingping; Zhang, Qinghua; Meng, Lirong; Lang, Bin; Hong, Yongfeng; Zhong, Chaoyue; Tian, Xun; Cui, Zifeng; Jin, Zhuang; et al. (Nucleic acids research, 2023)
Abstract Human papillomavirus (HPV) integration is a critical step in cervical cancer development; however, the oncogenic mechanism at the genome-wide transcriptional level is still poorly understood. In this study, we employed integrative analysis on multi-omics data of six HPV-positive and three HPV-negative cell lines. Through HPV integration detection, super-enhancer (SE) identification, SE-associated gene expression and extrachromosomal DNA (ecDNA) investigation, we aimed to explore the genome-wide transcriptional influence of HPV integration. We identified seven high-ranking cellular SEs generated by HPV integration in total (the HPV breakpoint-induced cellular SEs, BP-cSEs), leading to intra-chromosomal and inter-chromosomal regulation of chromosomal genes. The pathway analysis revealed that the dysregulated chromosomal genes were correlated to cancer-related pathways. Importantly, we demonstrated that BP-cSEs existed in the HPV–human hybrid ecDNAs, explaining the above transcriptional alterations. Our results suggest that HPV integration generates cellular SEs that function as ecDNA to regulate unconstrained transcription, expanding the tumorigenic mechanism of HPV integration and providing insights for developing new diagnostic and therapeutic strategies.